Administrative autonomy in India (Note) - Dubhashi, P.R. (1998)
Espousing concern for low level of administrative autonomy, the author illustrates briefly the tradition of autonomy that prevailed earlier to contrast it with the existing scenario. Before summing up the discussion, he suggests certain remedial measures which, according to him, can help improve the situation. - Reproduced
Keywords: Note; Public administration - India; Public administration